Integration of pastoral fencing areas in sheep breeding systems in the Algerian steppe. - Hadbaoui, Ilyes; Khaouani, Boumedienne; Berrabah, Djamel Edine; Safi, Rekia; Zemour, Hafidh (Annals of Arid Zone, 2023)
The aim of this novel study is to examine the incorporation of pastoral fencing areas as a forage resource in the management of sheep herds in the Algerian steppe areas. In the quest to reduce feed costs during specific periods, several sheep breeders in the Algerian steppe have resorted to rent pastoral fencing lands. The research methodology employed consists of interviews with fencing area renters and floristic surveys conducted prior to the opening period of the pastoral fencing. Fencing areas of M’Kimen and Saouas in Tiaret region were selected for this study due to its agropastoral potential. The findings of the study reveal that the problem of animal overstocking on rangelands is present even in rangelands controlled by fencing. In spite of the measures taken to control the fenced areas, the rangelands meet only a fraction of the feed requirements for the flocks, specifically 25% for M’Kimen and 38.4% for Saouas. The results of this investigation contribute to the scientific understanding of enhancing the management mechanisms of pastoral fencing lands and the overall development of sheep breeding programs in the steppe.